Effects of 60 Min Electrostimulation With the EXOPULSE Mollii Suit on Objective Signs of Spasticity - Pennati, Gaia Valentina; Bergling, Hanna; Carment, Loïc; Borg, Jörgen; Lindberg, Påvel G.; Palmcrantz, Susanne (Frontiers in Neurology, 2021)
Background: The EXOPULSE Mollii method is an innovative full–body suit approach for non-invasive electrical stimulation, primarily designed to reduce disabling spasticity and improve motor function through the mechanism of reciprocal inhibition. This study aimed to evaluate the effectiveness of one session of stimulation with the EXOPULSE Mollii suit at different stimulation frequencies on objective signs of spasticity and clinical measures, and the subjective perceptions of the intervention. Methods: Twenty patients in chronic phase after stroke were enrolled in a cross-over, double-blind controlled study. Electrical stimulation delivered through EXOPULSE Mollii was applied for 60 minutes at two active frequencies (20 and 30 Hz) and in OFF-settings (placebo) in a randomized order, every second day. Spasticity was assessed with controlled-velocity passive muscle stretches using the NeuroFlexor hand and foot modules. Surface electromyography (EMG) for characterizing flexor carpi radialis, medial gastrocnemius and soleus muscles activation, Modified Ashworth scale and range of motion were used as complementary tests. Finally, a semi-structured interview was conducted to assess the participants’ perceptions of using the EXOPULSE Mollii suit. Results: At group level, analyses showed no significant effect of stimulation at any frequency on NeuroFlexor neural component (NC) and EMG amplitude in the upper or lower extremities (p> 0.35). Nevertheless, the effect was highly variable at the individual level, with 8 patients exhibiting reduced NC (> 1 Newton) in the upper extremity after stimulation at 30 Hz, 5 at 20 Hz and 3 in OFF-settings. All these patients presented severe spasticity at baseline, i.e. NC > 8 Newton. Modified Ashworth ratings of spasticity and range of motion did not change significantly after stimulation at any frequency. Finally, 75% of participants reported an overall feeling of well-being during stimulation, with 25% patients describing a muscle-relaxing effect on the affected hand and/or foot at higher frequencies. Conclusions: Sixty minutes of electrical stimulation with EXOPULSE Mollii suit did not reduce spasticity consistently in the upper and lower extremity in the chronic phase after stroke. Findings suggest need for further studies in patients with severe spasticity after stroke including repeated stimulation sessions. Trial registration: NCT04076878, https://clinicaltrials.gov/ct2/show/NCT04076878. Retrospectively registered on 03/09/2019.